Factors influencing the impact of temporomandibular disorders on oral health-related quality of life among school children aged 12-15 years in Mangalore: An observational study - Swapna Sarit; Gururaghavendran Rajesh; B H Mithun Pai; Ramya Shenoy (Wolters Kluwer Medknow Publications, 2019)
Background: Temporomandibular disorders (TMDs) have been recognized as common orofacial conditions which cause considerable pain. Apart from dental caries and periodontal diseases, TMDs are becoming significant ailment affecting individuals due to their magnitude and impact on individuals. Few studies have examined the impact of TMDs on oral health-related quality of life (OHRQoL) in adolescents, especially in the Indian context. Aim: To assess the factors affecting the impact of TMDs on OHRQoL among 12 to 15-year-old schoolchildren in Mangalore. Materials and Methods: A cross-sectional study was carried out among 12 to 15-year-old schoolchildren in Mangalore. Signs and symptoms of TMDs and parafunctional habits were analyzed using a screening questionnaire recommended by the American Academy of Orofacial Pain. OHRQoL was measured by the 16-item version of Children Perception Questionnaire (CPQ11-14). Malocclusion was also assessed using Dental Aesthetic Index (DAI). Data were analyzed using Statistical Package for the Social Sciences (SPSS) software, version 14 (SPSS Inc., Chicago, IL, USA). Chi-square test and step-wise multiple logistic regression test were employed. P < 0.05 was considered statistically significant. Results: TMDs showed statistically significant association with OHRQoL among the schoolchildren (P < 0.05). Parafunctional habits and malocclusion were also significantly associated with both TMDs and OHRQoL among the study participants. Multivariate analysis found few parafunctional habits and malocclusion to be the significant predictors for both TMDs and OHRQoL (P < 0.05). Conclusion: Parafunctional habits, malocclusion, and TMDs had statistically significant association with OHRQoL. Parafunctional habits and malocclusion were found to be significant predictors for both TMDs and OHRQoL. TMDs and the associated factors have an impact on the psychosocial functioning of the children. This study emphasizes the importance of OHRQoL assessment for evaluating TMD patients because it can have a substantial impact on functional, emotional and psychologic aspects, thus negatively affecting the OHRQoL of children.